Link Adaptation Algorithms for Dual Polarization Mobile Satellite Systems - Anxo Tato; Pol Henarejos; Carlos Mosquera; Ana Pérez-Neira (9th EAI International Conference on Wireless and Satellite Systems, WISATS, 2017)
The use of dual polarization in mobile satellite systems is very promising as a means for increasing the transmission capacity. In this paper a system which uses simultaneously two orthogonal polarizations in order to communicate with the users is studied. The application of MIMO signal processing techniques along with Adaptive Coding and Modulation in the forward link can provide remarkable throughput gains up to 100 % when compared with the single polarization system. The gateway is allowed to vary the MIMO and Modulation  and Coding Schemes for each frame. The selection is done by means of a link adaptation algorithm which uses a tunable margin to achieve a predefined target Frame Error Rate.